Malaysian public private partnership projects: success factors and risks affecting project success and moderating role of risk management - Ahmad, Usman (2019)
Public-Private Partnership (PPP) is considered as the main tool in the allocation of infrastructure and public services worldwide. The Malaysian government has implemented Public Private Partnership (PPP) since 1980s for the development of infrastructure. However, records showed that some PPP projects failed to achieve their objectives. As PPP arrangements support the government efforts in development, it is critical to identify the risk factors and success factors that affect the PPP projects and the role of risk management in PPP project success. Thus, this study examines the impact of success factors and risk factors on PPP project success, as well as the moderating role of risk management in the relationship between risks and project success. This study also validates the measurement items for the PPP project success and PPP risk management practices in Malaysia. The study employs a quantitative research design and the data has been obtained through interviews and surveys. The Exploratory Factor Analysis (EFA) and Partial Least Square were applied (PLS) for data analysis. The study reveals that the agreement and design concept play a vital role in PPP risk management. Moreover, all five success factor categories and five risk categories are found affect PPP project success. Risk management is found to be significantly moderate the relationship between risks and PPP project success. The findings of the study contribute to the understanding of PPP project success and risk management by adding new items in the constructs, as well as categorizing the success factors into five categories. In addition, the study contributes to the knowledge of PPP by highlighting the risk categories that affect PPP project success.